日本人患者におけるCYP2D6遺伝子多型がVenlafaxineおよびその代謝物の薬物動態に及ぼす影響について - 加藤, 和子; 佐々木, 太郎; 佐々木, はづき; 古郡, 規雄; 井上, 義政; 黒田, 仁一; 下田, 和孝; 渡邊, 崇; 篠﨑, 將貴; 林, 有希 (日本薬理学会年会要旨集, 2020)
Purpose This study evaluated the impact of CYP2D6*10 alleles on the steady-state plasma concentrations of venlafaxine (VEN) and its metabolite O-desmethylvenlafaxine (ODV) in Japanese psychiatric patients. Methods All patients received VEN once daily before bedtime over 1 weeks to achieve a steady-state concentration. About 10 to 15 hours after the final dose, venous blood sampling was performed. Three patients with CYP2D6*5 allele [*1/*5 (n=1), *5/*10 (n=2)] were excluded from the analysis to eliminate the effect of the CYP2D6*5 allele. Finally, 41 data from 41 patients were included in the study. The plasma concentrations of VEN, ODV, S-VEN, R-VEN, S-ODV and R-ODV were measured using the high-performance liquid chromatography. The CYP2D6 genotypes were determined by polymerase chain reaction. Results Multiple regression analyses including sex and age revealed that positive and significant correlations were found between age, and the steady-state plasma concentrations corrected by body weight for VEN(p=0.004), ODV(p=0.002), S-VEN (p=0.035), R-VEN (p=0.033) and S-ODV (p=0.015), respectively. Positive and significant correlations were found between the number of CYP2D6*10 alleles, and the plasma concentrations corrected by body weight for VEN (p=0.008) and S-VEN (p=0.001), respectively. Conclusion CYP2D6*10 and age might influence the pharmacokinetics of VEN and its enantiomeric metabolites.